A new species of Alloperla (Plecoptera: Chloroperlidae) from China - Li, Weihai; Wang, Rongfeng (Zootaxa, 2011)
A chloroperline stonefly species from Liaoning Province, northeastern China is described as new to science: Alloperla yangi sp. n. Its taxonomic relationship to similar species is discussed.